Flocking Dynamics for Cooperation-Antagonism Multi-Agent Networks Subject to Limited Communication Resources - Shi, Lei; Ma, Zhuangzhuang; Yan, Shuaiming; Ao, Tianyong (IEEE transactions on circuits and systems. I, Regular papers, 2024)
This contribution explores the flocking dynamic behavior of multi-agent networks with limited communication resources, where there are both cooperative and antagonistic relationships among agents. Taking into account the shortage of communication resources, a distributed control protocol with edge-asynchronous communications is designed, in which only part of the communication links are awakened at each time instant to perform information transmission. A product approach of super-stochastic matrices is utilized to rigorously check the convergence of the dynamic model. With this method, algebraic conditions on cooperative and antagonistic relationships among agents are established so that the entire multi-agent network emerges with flocking dynamics. At last, theoretical results are tested and verified through computer simulations.